1999
DOI: 10.1021/ja983712m
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pH-Induced Morphological Changes in Aggregates of Polystyrene-block-poly(4-vinylpyridine) in DMF/H2O Mixtures

Abstract: Multiple changes in the aggregate morphologies of polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) diblocks have been observed as a function of the apparent pH (pH*) in DMF/H2O mixtures. The pH* changes were induced by adding HCl (in the concentration range 400 nM−20 mM) or NaOH (100 nM−20 mM). On the acid side, as the pH* increases from 7 (20 mM HCl) to 12.3 (the pH* of the original polymer solution without any additional microions), the aggregate morphology changes from large compound micelles (LCMs) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
290
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 286 publications
(300 citation statements)
references
References 15 publications
6
290
0
4
Order By: Relevance
“…The diblocks associate to form a hydrophobic core, thereby minimizing the unfavorable interaction with water, while the charged blocks form a highly charged corona or brush [96]. The micelle morphology depends on different parameters.…”
Section: Additional Effectsmentioning
confidence: 99%
“…The diblocks associate to form a hydrophobic core, thereby minimizing the unfavorable interaction with water, while the charged blocks form a highly charged corona or brush [96]. The micelle morphology depends on different parameters.…”
Section: Additional Effectsmentioning
confidence: 99%
“…PEO-Br macroinitiator was prepared according to previous work [17,18]. 1 H NMR study in CDCl 3 indicated that the hydroxyl end group of the PEO was fully esterified (data not shown).…”
Section: Synthesis Of Macroinitiator and Peo-b-phema Copolymermentioning
confidence: 99%
“…PEO-Br macroinitiator was prepared according to literature [17,18]. 0.55 g PEO-Br macroinitiator (0.26 mmol), 3.2 mL of HEMA (3.4 g, 0.026 mol), 2 mL of methanol, 0.0832 g of bpy (0.53 mmol) and 0.0059 g of CuBr 2 (0.026 mmol) were placed into a dried glass tube with a magnetic bar and degassed three times with freeze-pumpthaw cycle.…”
Section: General Procedures For Polymerization From Macroinitiatormentioning
confidence: 99%
See 1 more Smart Citation
“…Micelles have demonstrated a variety of shapes such as spheres, rods, vesicles, tubules, and lamellae depending on the relative length of hydrophobic/hydrophilic blocks as well as solvent environment (6)(7)(8). Morphology of micelles has significant impact on the pharmacokinetic properties of micelles.…”
Section: Introductionmentioning
confidence: 99%